A mathematical model for scheduling of production process and allocation of an automatic guided vehicle in a flexible manufacturing system. (2018) - Tavakoli, Mohammad Mehdi; Haleh, Hasan; Mohammadi, Mohsen
Given that material handling in manufacturing systems is very important, many organisations use automatic guided vehicle (AGV). In recent years, many organisations have intended to have access to an optimal scheduling plan for their manufacturing and transportation system. For this reason, a mathematical model is proposed in this study for scheduling of the production process and AGV's allocation. Production time in any process, setup time, loaded/unloaded trip duration, parking spaces, and the discharge time and loading of products at each workstation are considered in the proposed model. Finally, a numerical example is used to explore the proposed model and it will be solved using GAMS software.